Improving breed‐and‐release programmes in the face of a threatening pathogen, Batrachochytrium dendrobatidis. Issue 10 (19th August 2021) - Klop‐Toker, Kaya L.; Valdez, Jose W.; Stockwell, Michelle P.; Fardell, Loren; Clulow, Simon; Clulow, John; Mahony, Michael J.
Abstract: As the proportion of threatened species increases, so too does the need for effective conservation strategies. In response, captive breed‐and‐release and habitat mitigation programmes are two conservation actions that are increasing in use and effectiveness. Success of these programmes is frequently hampered by the continued presence of threatening processes. In the case of amphibian reintroductions, a key threatening process that is difficult to eliminate is the deadly fungal pathogen, Batrachochytrium dendrobatidis (Bd). This pathogen is the proximate cause of decline for the threatened green and golden bell frog, Litoria aurea, and has contributed to the failure of previous breed‐and‐release programmes of this amphibian. To investigate whether is it possible to establish a captive‐bred population of L. aurea that could persist in the presence of Bd, a breed‐and‐release programme was conducted in a created habitat that included increased salinity to inhibit fungal growth rates, exclusion of potential reservoir hosts and source animals bred from parents 'experienced' with the strain of Bd present in the release environment. The population persisted in the created habitat for more than 4 years (the timescale of monitoring) but suffered higher infection levels compared with nearby extant populations of L. aurea . These infections significantly reduced apparent survival. Infection dynamics were linked to temperature, host density in the previous season, and size and age of the host, and these factors differed from those in extant populations and are likely to have contributed to the high levels of Bd infection at the created site. This article discusses how it may be possible to manipulate these factors to improve the success of future breed‐and‐release programmes, and recommends the construction of warm water bodies and a strategy of prioritizing the release of fewer, large propagules of high body condition and mixed‐age class, over large numbers of younger, smaller animals.